"DIGNATIC" MULTIMEDIA PERSONAL MEDIA FOR PKn LEARNING IN HIGH SCHOOL - Lavinia Puspitasari (JOSAR (Journal of Students Academic Research), 2021)
Abstrak This research is motivated because the results of the 1st Semester Final Examination of Civics Education are the lowest results. The reasons for this include lack of motivation and interest that is not like other subjects. Limited resources and too much material, while teachers have not used multimedia-based media as learning support media, even though the school has LCD Projector facilities that can be used for the learning process. This study aims to develop learning media, find out the feasibility of the media, and find out the differences in learning outcomes before and after using multimedia-based learning media using Adobe Flash in the material values ​​of Pancasila in the practice of administering Civics subjects in class X of SMA 4 Blitar. This type of research is Research and Development (R and D) with the development method. Determination of the feasibility level of multimedia-based learning media based on expert validation tests and small-scale trials was then applied to the sample class. Data collection techniques using interviews, documentation data, questionnaires, and tests. Learning outcomes of small-scale trials have increased with the acquisition of understanding in the criteria of being. Questionnaire students' responses state if the media are in very good criteria and questionnaire teacher responses are in good criteria. It is proven that there is an increase in student learning outcomes with an average value of pre test class X IIS 5 of 37 and an average value of post test 80, while the pre test value for class X IIS 6 is 48 and the post test average value is 86.